A THIRST FOR POWER: A GLOBAL ANALYSIS OF WATER CONSUMPTION FOR ENERGY PRODUCTION. - Spang, Edward. (2017)
Abstract: Producing energy resources requires significant quantities of freshwater. As an energy sector changes or expands, the mix of technologies deployed to produce fuels and electricity determines the associated burden on regional water resources. A number of reports exist that specify water consumption by discrete energy production technologies. This research synthesizes and expands this previous work by examining the global distribution of water consumption intensity of national-level energy portfolios. By defining and calculating indicators to quantify the relative water use intensity of national energy systems, it was possible to highlight potentially problematic areas of high water use intensity while also providing examples of water-efficient energy production. The results of the research show a high variability in the national water consumption of energy production (WCEP) for the 158 countries that were assessed. However, looking across the indicators for WCEP internationally, the countries that were heavily producing fossil fuel or biofuels demonstrated the greatest intensity of energy-based water consumption. The economic imperative to develop fossil fuels drives high water consumption in countries that already lack sufficient water supplies. Meanwhile, biofuels require so much water over their lifecycle per unit of produced energy that any modest commitment to producing biofuels has significant water consumption ramifications for the country. While these results are based on a comprehensive review of available data, future research in this area could be significantly enhanced through better data and widespread adoption of consistent reporting mechanisms. Additional opportunities to expand the field include increasing the resolution of the study regions, tracking these indicators over time, and exploring innovative policy approaches to managing national WCEP effectively. For nations facing the greatest limitations in the availability of local water and energy resources, the need for efficient use of these resources is imperative. Indeed, many countries are already operating at the frontier of their fragile local energy and water systems. By defining new metrics to evaluate the intensity of water use for energy production, this research can influence and improve policy-making for more secure and sustainable water and energy resource management.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: William Moomaw.; Committee: Kelly Gallagher, Paul Kirshen, and David Marks.; Keywords: Water resources management, Energy, and International relations.